Study on clinical profile of ventilated children in a pediatric intensive care unit of tertiary care centre - S. N., Pushpa; Savaskar, S. V.; Ansari, Aatif; Parmar, Manish (International Journal of Contemporary Pediatrics, 2023)
Background: Mechanical ventilation constitutes a major therapeutic modality in intensive care, so care of patients requiring ventilatory support is an integral part of the critical care unit. Very less data is available from developing countries regarding use of Mechanical Ventilation, its complication and outcomes which is a challenge for modern day intensivists. Objectives were to study clinical profile of ventilated children in a PICU of tertiary care centre. Methods: Present prospective cross-sectional study was conducted on ventilated children admitted at PICU of Dr. VMGMC hospital, Solapur. The study included demographics, clinical profile, indication for ventilation, length of hospital stays, outcome. Results: Out of 300 children, 170 were males. Most the children were from age group <5 years. Difficulty in breathing was seen in 188 cases, fever in 55%, 100 patients had acute CNS infections, 82 cases had bronchopneumonia, 85 cases respiratory failure was the indication for intubation. The duration of the mechanical ventilation was more in CNS cases, RS cases, sepsis cases. 165 cases got recovered successfully. Conclusions: Mechanical ventilation is one of the major supportive modalities used in critical care all over the world and is also used in many of the sick children in government tertiary care centre. Despite of its life saving advantages, mechanical ventilation is associated with complication. Early use of HHFNC, CPAP/BiPAP and other non-invasive modes of ventilation decrease the need for invasive mechanical ventilation.